Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China - Mo, Raorao; Yan, Yanhua; Wang, Guoquan; Li, Weihai; Murányi, Dávid (Zootaxa, 2019)
A new species of the species rich Asian perlid genus Kamimuria Klapálek, K. peppapiggia sp. n. from Henan Province of northwestern China, is described based on the male, female, larva, and egg. Relationship with congeners are discussed based on morphological characters. The new species is a possible remnant of the once diverse lowland aquatic fauna of the North China Plain.